Adsorptive performance of congo red using copper-aluminum LDHS load to rice husk biochar - Palapa, Neza Rahayu; Novie Juleanti,; Normah,; Mohadi, Risfidian; Rachmat, Addy; Lesbani, Aldes; Taher, Tarmizi (Penerbit Universiti Kebangsaan Malaysia, 2022)
This work aimed that CuAl layered double hydroxide (LDH) is loaded to biochar to form CuAlLDH@BC composites by co-precipitation methods. CuAlLDH@BC composite was prepared and characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, surface area specific analysis BET method, thermalgravimetric, and scanning electron microscopy (SEM) for morphological analysis. CuAlLDH@BC composite used as adsorbent for the removal of Congo red. The adsorption ability of CuAlLDH@BC composite evaluated by pseudo-second-order kinetic model, with Qecalculated and Qeexperimental of the composite were closed (47.619 and 46.143 mg/g, respectively). Furthermore, the adsorption conducts were more consistent with the Langmuir isotherm model, than the Freundlich isotherm model. The isotherm adsorption data obtained the maximum adsorption capacity was 61.350 mg/g. Thermodynamic studies illustrated the endothermic nature of CuAlLDH@BC, as well as the fact that the adsorption process is spontaneous. Thus, CuAlLDH@BC showed a high reusability performance even after third cycle of adsorption-desorption process.